2009
DOI: 10.3892/ijo_00000388
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of SOS1 is detected in prostate cancer epithelial cells from African-American men

Abstract: Abstract. African-American (AA) men experience an increased risk of developing prostate cancers as well as increased mortality following treatment as compared to European-American (EA) men. The aim of our study was to identify biological factors with the potential to predispose AA men to prostate tumor progression and metastasis. To identify cancer-specific gene expression patterns in AA men, we established primary prostate cancer epithelial cells from 14 AA and 13 EA men. High-throughput microarrays were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In addition, Son of Sevenless 1 (SOS1) is an activator of Ras/MAPK, which is overexpressed in AA prostate cancer cells. SOS1 increased levels caused higher cancer cell proliferation and migration through increased activation of ERK signaling pathways (Timofeeva et al, 2009). PI3K-AKT is one of the most important signaling pathways, which is differentially activated among different races and may modulate the mTOR pathway in several human cancers.…”
Section: Mtor/erk-1/2-associated Signaling Molecules and Racial Disparitymentioning
confidence: 99%
“…In addition, Son of Sevenless 1 (SOS1) is an activator of Ras/MAPK, which is overexpressed in AA prostate cancer cells. SOS1 increased levels caused higher cancer cell proliferation and migration through increased activation of ERK signaling pathways (Timofeeva et al, 2009). PI3K-AKT is one of the most important signaling pathways, which is differentially activated among different races and may modulate the mTOR pathway in several human cancers.…”
Section: Mtor/erk-1/2-associated Signaling Molecules and Racial Disparitymentioning
confidence: 99%
“…Microarray analyses of 69 clinically matched patients with prostate cancer demonstrated differences in gene expression profiles of prostate tumors from AA and CA men, particularly in genes related to tumor immunobiology ( 9 ). Our previous report of gene expression in prostate epithelial cells from AA and CA men show differences in the expression of genes affecting tumor aggressiveness and metastases using high-throughput microarray assays ( 8 ). These observations support primary epithelial cultures as a useful tool for discovering molecular mechanisms underlying health disparities in prostate cancer; however, the cultures permitted <5 passages, followed by cell senescence and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The current study found that expression of SOS1 and its downstream, JNK2, c-JUN, and MMP9, were induced by oxidative stress in HCC cells. Consistence with the study by Timofeeva et al, they showed that SOS1 was overexpressed in prostate cancer cells, and it was associated with increased cell migration and invasion (127). These data suggested that elevated SOS1 may be linked to enhanced aggressiveness of tumor cells.…”
mentioning
confidence: 53%